2019
DOI: 10.3390/medicina55100645
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection and Psoriasis: A Systematic Review and Meta-Analysis

Abstract: Background and Objectives: To perform a systematic review and meta-analysis with the aim of determining the relationship between H. pylori infection and psoriasis. Methods: Pubmed, Embase, China National Knowledge Infrastructure (CNKI), and Web of Science were searched for articles published up to July, 2019. Review Manager 5.3 and Stata 12.0 were used for statistical analyses. Results: The initial database search resulted in 204 articles. Through exclusion and screening, 11 studies involving a total of 1741 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 31 publications
0
20
0
1
Order By: Relevance
“…The bioavailability of the prodrug is <7%, the rest being eliminated in the feces. After its absorption in the proximal small bowel, dabigatran etexilate reaches the liver where it is transformed into the active form after its cleavage by the serum and hepatic esterases (10). According to its pharmacokinetics, one can accept that the lower GI bleedings are more frequent with dabigatran, due to its topical effect on the mucosa leading to bleeding, especially on pre-existing gut lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The bioavailability of the prodrug is <7%, the rest being eliminated in the feces. After its absorption in the proximal small bowel, dabigatran etexilate reaches the liver where it is transformed into the active form after its cleavage by the serum and hepatic esterases (10). According to its pharmacokinetics, one can accept that the lower GI bleedings are more frequent with dabigatran, due to its topical effect on the mucosa leading to bleeding, especially on pre-existing gut lesions.…”
Section: Discussionmentioning
confidence: 99%
“…6 A systematic review evaluated the relationship between H pylori infection and obesity among Chinese adults. The prevalence of H pylori was 42% (95% CI, [37][38][39][40][41][42][43][44][45][46][47] and mean difference of BMI between subjects with and without H pylori infection was 0.94 (95% CI, −0.04 to 1.91). The OR value was 1.20 (95% CI, 1.13-1.…”
Section: Metabolic Syndrome and Obesitymentioning
confidence: 99%
“…Moreover, H pylori prevalence increased significantly in patients with moderate and severe psoriasis (OR, 2.27; 95% CI, 1.42-3.63). 41 Another recent meta-analysis found that in H pylori-positive patients, antibiotic treatment induced chronic spontaneous urticaria remission independently of H pylori eradication. 42 In a prospective study, 57 consecutive patients (27 pityriasis versicolor, 30 telogen effluvium) screened for anti-H pylori and anti-CagA IgG, showed significantly higher rates of H pylori positivity in the pityriasis versicolor group than in the telogen effluvium group (P < .05).…”
Section: S K In D Is E a S E Smentioning
confidence: 99%
“…Its association with H. pylori infection had already been investigated with the search for antibodies against H. pylori in patients with psoriasis without known gastrointestinal complaints[ 65 ]. Recently, a meta-analysis found a strong evidence demonstrating this association (OR = 1.19, 95%CI: 1.15-2.52, P = 0.008) and highlighted that the rate of H. pylori infection, interestingly, was significantly high in patients with moderate and severe psoriasis (OR = 2.27; 95%CI: 1.42-3.63, I 2 = 27%) but not in patients with the milder disease (OR = 1.10; 95%CI: 0.79-1.54, I 2 = 0%)[ 66 ]. Another disease commonly associated with H. pylori infection is chronic urticaria, a clinical condition that presents with itchy, erythematous or swollen urticaria[ 67 , 68 ].…”
Section: Extragastric Manifestationsmentioning
confidence: 99%